Promoting interconnections between reflective practice and collective creativity in higher arts education: the potential of engaging with a reflective matrix. Issue 4 (4th July 2021) - Treacy, Danielle; Gaunt, Helena
ABSTRACT: Reflective practice has long been understood to be integral to the arts, but has predominantly been conceptualised in terms of tacit or individual activity. Identifying the need to reimagine and deepen reflective practice in higher arts education as explicit, collaborative, and integrally connected to artistic practice, this article explores the potential of a reflective matrix focused on ensemble practices, teamwork and collaborative learning in the arts for promoting interconnections between reflective practice and collective creativities. The article reports on a collaborative research approach based on in-depth interviews with 12 professors and lecturers of dance, music, theatre, and visual arts from the University of the Arts Helsinki, Finland that were analysed in stages using the reflective matrix. The results demonstrate how working with the matrix provided opportunities for extending understandings of ensemble practices and particularly of the collective creativities within them. Insights gained include the ways in which our iterative and dialogic way of engaging with the matrix challenged our initial expectations and deepened our understandings of two professional dilemmas: engaging with an audience and navigating correctness. The article concludes by attending to the implications of our approach for both research and practice in higher arts education.